Late Diagnosis of Narcolepsy With Cataplexy: A Novel Case of Cataplectic Facies Presenting in an Elderly Woman - Khalsa, Sakh (J Clin Sleep Med, 2019)
Cataplectic facies is an unusual feature described in children with narcolepsy and cataplexy. The typical manifestations of cataplectic facies consist of repetitive mouth opening, tongue protrusion, and ptosis. An interesting observation is that the usual emotional triggers associated with cataplexy such as laughter and joking are not always present, thus hampering diagnosis of the underlying syndrome. Cataplectic facies is thought to be a phenomenon observed in the early stages of narcolepsy type 1 and is thought to disappear by the time the patient reaches puberty. We present a unique case of an elderly woman with narcolepsy type 1 demonstrating cataplectic facies. The novel circumstances of this case highlight that facial cataplexy can present later in life, in contrast with previous descriptions that report resolution of cataplectic facies before puberty. Wider recognition of these features throughout the life course may aid in accurate diagnosis and thereby ensure swift access to appropriate treatment. CITATION: Khalsa S, Qureshi K, Bagshaw AP, Rather A. Late diagnosis of narcolepsy with cataplexy: a novel case of cataplectic facies presenting in an elderly woman. J Clin Sleep Med. 2019;15(11):1687–1690.